Hubungan Antara Tingkat Penggunaan Media Sosial dengan Tingkat Produktivitas Mahasiswa dalam Menyelesaikan Tugas Akademik - Suci Ramadhani; Surya Alenta Nababan; Yasmin Azzahra; Sisti Nadia Amalia (PT. Sharia Journal and Education Center, 2024)
Social media has become an integral part of students' lives, serving as a tool for communication, a source of information, and a means of entertainment. This study aims to analyze the relationship between the level of social media usage and students' productivity in completing academic tasks. The research employs a descriptive correlational quantitative approach, with data collected through online questionnaires using ordinal scales. The respondents were active students from various universities. The analysis was conducted using Spearman's Rank correlation test and the t-test for significance. The results show a moderate positive relationship between social media usage and academic productivity, with a Spearman's Rank correlation coefficient (rₛ) of 0.483. The significance test indicates a t-value of 3.819, which is greater than the critical t-value of 1.677 at the 5% significance level. This demonstrates that the relationship found is statistically significant. The study concludes that prudent use of social media can contribute to enhancing students' productivity in completing academic tasks, although the relationship is not particularly strong. The implications of this study highlight the importance of time management and social media activity regulation to optimally support academic productivity.